2003
DOI: 10.1046/j.1365-2117.2003.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal history of the Cretaceous Sindong Group, Gyeongsang Basin, Korea based on fission track analysis

Abstract: Apatite and zircon fission track (FT) analyses were carried out to reconstruct the thermal history of the Lower Cretaceous Sindong Group, which is the lowermost stratal unit of the Gyeongsang Basin, Korea. Zircon FT central ages show a wide range from 83 + 5 to 157 + 18 Ma, and single-grain age spectra have multiple age populations, whereas all apatites have very consistent FT ages of c. 60 Ma, suggesting a totally reset cooling age. Co-existence of both older and younger ages compared with the depositional ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…The average cooling age and temperature are based on apatite fission track of Jurassic and Cretaceous granites (Jin et al . 1987; Lim & Lee 2005) and Cretaceous basins (Lim et al . 2003; Choi & Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average cooling age and temperature are based on apatite fission track of Jurassic and Cretaceous granites (Jin et al . 1987; Lim & Lee 2005) and Cretaceous basins (Lim et al . 2003; Choi & Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Apatite fission track analyses for Daebo granites (Jin et al . 1987), Cretaceous basins (Lim et al . 2003; Choi & Lee 2006) and Cretaceous Palgongsan Granite located in the Cretaceous Gyeongsang Basin (Lim & Lee 2005) suggest that they were uplifted to a shallow level of the apatite partial annealing zone of 60–110°C at 70–50 Ma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…track length distribution within a sample), and (3) the chlorine composition. The original basis of this approach, based on age and length data only, is described in several key publications Laslett et al, 1987;Green et al, 1989a), which have served as the basis for most fission-track application studies in the last 20 years Issler et al, 1999;Gleadow et al, 2002;Osadetz et al, 2002;Lim et al, 2003;Stockli et al, 2003).…”
Section: Basis Of Fission-track Technologymentioning
confidence: 99%
“…2003). From apatite and zircon fission‐track analyses of the Sindong Group, Lim et al . (2003) suggested that the Sindong Group was heated into the zircon partial annealing zone around 80 Ma and cooled below the apatite closure temperature at ca 60 Ma.…”
Section: Introductionmentioning
confidence: 99%